Hand function and type of grasp used by chronic stroke individuals in actual environment - Demartino A.M.* (2019)
© 2019, © 2019 Taylor & Francis Group, LLC.Background: Knowledge of paretic upper limb (UL) use in the actual environment is crucial for defining treatment strategies that are likely to enhance performance. Objective: To quantify the hand function and type of grasp performed in the actual environment following stroke and determine if any differences in hand use are dependent on the degree of motor impairment. Method: This cross-sectional study enrolled 41 participants with chronic hemiparesis classified as having either mild (11), moderate (20), or severe (10) UL impairment. A behavioral map was used while observing hand use over the 4-h experimental period, during which we checked: activity- unimanual, bimanual or non-task-related; hand function- stabilization, manipulation, reach-to-grasp, gesture, support or push; and type of grasp- digital or whole-hand. Results: Participants with severe impairment did not use the paretic UL spontaneously; analyzing the moderate and mild subgroup together, the predominant UL hand functions were stabilization and manipulation, the paretic UL performs the stabilization function using the whole-hand more frequently (71.2%) than digital (28.8%) grasp. In the subgroup analysis, the paretic and non-paretic UL in the moderate and the paretic UL in the mild subgroup perform the whole-hand stabilization more frequently than digital. Digital grasp is more accomplished by the non-paretic UL in reach-to-grasp hand function, particularly in the mild subgroup. Conclusion: The paretic UL is predominantly employed for stabilization function using a whole-hand grasp. The type of grasp in the actual environment is affected by motor impairment, and greater motor impairment leads to the performance of less complex tasks.